2020
DOI: 10.1177/2050312120965752
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines in the pathogenesis of cardiovascular disease and cancer

Abstract: Inflammatory cytokines are highly inducible small glycoproteins or regulatory proteins of low molecular weight secreted by different cell types. They regulate intercellular communication and mediate a number of physiological functions in the human immune system. Numerous prospective studies report that inflammatory cytokines strongly predict coronary artery disease, myocardial infarction, heart failure and other adverse cardiac events. Inflammatory cascade is believed to be a causative factor in the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 144 publications
(206 reference statements)
2
78
0
1
Order By: Relevance
“…This connection is key to consider, as risk of comorbidities, and particularly, cardiovascular diseases, which have been linked to higher activity involving innate immune system functions. 76 Significant interplay can also be observed in prior studies, as pre‐existing chronic conditions such as obesity may additionally have strong associations with other prognostic factors for worse COVID‐19 outcomes such as CVD, respiratory disease, diabetes, and renal disease. 77 …”
Section: Discussionmentioning
confidence: 94%
“…This connection is key to consider, as risk of comorbidities, and particularly, cardiovascular diseases, which have been linked to higher activity involving innate immune system functions. 76 Significant interplay can also be observed in prior studies, as pre‐existing chronic conditions such as obesity may additionally have strong associations with other prognostic factors for worse COVID‐19 outcomes such as CVD, respiratory disease, diabetes, and renal disease. 77 …”
Section: Discussionmentioning
confidence: 94%
“…Coronary stenting is quite common in lung GGN patients with elevated levels of IL-6, which may re ect that in ammatory mediators could be implicated in aggravating coronary arterial damage. Higher levels of IL-6 and TNF-α participate in coronary arterial damage, as well as in the development and progression of tumors [27,28]. Besides, IL-6 also mediates the systemic in ammatory response of cancer patients [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms governing some pathways have been illustrated by in vitro studies or animal studies, many cytokines were found to be elevated in patients with cancer or tumor microenvironments [ 25 , 26 ]. Thus, it is of vital importance to fully explore how these cytokines interact with tumor cells and the tumor microenvironment, as a deep understanding of the underlying mechanisms and pathways could shed substantial light on the development of potential anticancer therapies.…”
Section: Inflammation and Cancermentioning
confidence: 99%